2002
DOI: 10.1002/em.10051
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of breast cancer: Polycyclic aromatic hydrocarbons as risk factors

Abstract: In the absence of a causal relationship between the incidence of sporadic breast cancer and occurrence of mutations in breast cancer susceptibility genes, efforts directed to investigating the contribution of environmental xenobiotics in the etiology of sporadic mammary neoplasia are warranted. Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous pollutants, which have been shown to induce DNA damage and disrupt cell cycle progression. In this report we discuss published data pointing to PAHs as a risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 53 publications
2
39
0
4
Order By: Relevance
“…To date, no mutations in the BRCA-1 gene have been identified in sporadic breast cancers, whereas the expression levels of BRCA-1 in breast tumors are lower than those observed in normal mammary tissue (45). Recent work by Jeffy et al (46) suggest that BP, a carcinogenic PAH found in tobacco smoke, environmental pollution, and foods may contribute to breast carcinogenesis through the inhibition of the tumor suppressor gene BRCA-1. Under the experimental conditions used in our study, the global gene expression analysis revealed no alterations in the tumor suppressor gene BRCA-1; however, Jeffy et al (15) in a study of BRCA-1 expression in MCF-7 cells, did see a decrease after 72 hours of BP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no mutations in the BRCA-1 gene have been identified in sporadic breast cancers, whereas the expression levels of BRCA-1 in breast tumors are lower than those observed in normal mammary tissue (45). Recent work by Jeffy et al (46) suggest that BP, a carcinogenic PAH found in tobacco smoke, environmental pollution, and foods may contribute to breast carcinogenesis through the inhibition of the tumor suppressor gene BRCA-1. Under the experimental conditions used in our study, the global gene expression analysis revealed no alterations in the tumor suppressor gene BRCA-1; however, Jeffy et al (15) in a study of BRCA-1 expression in MCF-7 cells, did see a decrease after 72 hours of BP treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PAH bind to DNA forming PAH-DNA adducts, initiating mutagenesis and carcinogenesis (Lijinsky, 1991;Jeffy et al, 2002). Interindividual differences in DNA adduct formation of persons who are exposed to the same external levels suggest that differences in absorption, activation and detoxification mechanisms, DNA repair, cell turnover, cellcycle control, as well as lifestyle or diet can modify individual response to exposure (Harris et al, 1982;Santella, 1999;Wiencke, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Covariates we considered as potential effect modifiers included menopausal status, season of the blood draw, length of residence in the interview home, age at diagnosis, active cigarette smoking, a combined measure of active cigarette smoking and exposure to passive smoking (from the parent or spouse) in the home, alcohol intake, and intake of grilled or smoked foods (as assessed in the main questionnaire). 8 An additional covariate we considered as a potential effect modifier was a measure of total dietary benzo[a]pyrene (BaP), which is one of the major components of PAH 20 and an established carcinogen. 5 The measure used in this analysis was a modification of a PAH food index developed recently by Kazerouni et al 21 that uses data collected as part of the diet history.…”
mentioning
confidence: 99%